WOMEN’S LANGUAGE FEATURES USED BY ELSA AND ANNA IN FROZEN II MOVIE - Tombang, Nopita; Arifin, M. Bahri; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This study aims to find women’s language features used by Elsa and Anna in Frozen II movie using Lakoff’s theory. This research used the qualitative method. The data were generated from the movie and movie scripts in the form of utterances and conversations expressed by Elsa and Anna. The researcher generated the data from the movie and movie script in the utterances and conversation. The result of the study showed that there were 35 data that contained women’s language features in the movie. There were nine types of women’s language features found in the movie. The women’s language features were found in the movie are Lexical hedges or filler, tag question, rising intonation, and empty adjective, intensifier, hypercorrect, superpolite, avoidance of strong words, and emphatic stress. In this movie, lexical hedges or fillers are the dominant women’s language features were found in this research.